Innovative and traditional health saving techniques in physical culture and sport - Elena A. Batalova, Galina I. Semenova, Alexej V. Shikhov, Petr A. Grigorev, (Opción, 2019)
The paper discusses the efficiency of using health saving techniques in physical culture, sports, and fitness. The leading method was a pedagogical experiment, which proved the effectiveness of using innovative and traditional methods in fitness training. We revealed the positive impact of suspended and rotational functional training on weight control, and of power pilates and strength training on slouching elimination. In conclusion, a sociological survey of those engaged in various types of fitness revealed a significant improvement in health indicators through the use of functional training, workout and power pilates and other innovative techniques combined with traditional approaches.